2018
DOI: 10.1007/s11251-018-9474-0
|View full text |Cite
|
Sign up to set email alerts
|

Fading distributed scaffolds: the importance of complementarity between teacher and material scaffolds

Abstract: Designing learning environments with distributed scaffolding —support distributed across different instructional tools, activities, and the teacher—can help support students’ different needs, but a critical question is how the design incorporates the hallmark feature of responsive support. While most material scaffolds in instructional tools are inherently static, teachers can complement support provided in material scaffolds by providing responsive assistance and mediating students’ int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 50 publications
(139 reference statements)
2
20
0
Order By: Relevance
“…Similarly, the verbal counts of the chat data indicated that soft scaffolds provided by facilitators often included attending to accountable talk and the regulation of the inquiry process. These results support prior work that highlight that scaffolds can work together in synergy to support similar functions (Martin, Tissenbaum, Gnesdilow, & Puntambekar, 2019; Reiser & Tabak, 2014). Interaction analysis indicated that hard scaffolds were a good starting point to uncover gaps in students' understanding, be it in terms of their conceptualization of the issue or support engagement in desired practices.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, the verbal counts of the chat data indicated that soft scaffolds provided by facilitators often included attending to accountable talk and the regulation of the inquiry process. These results support prior work that highlight that scaffolds can work together in synergy to support similar functions (Martin, Tissenbaum, Gnesdilow, & Puntambekar, 2019; Reiser & Tabak, 2014). Interaction analysis indicated that hard scaffolds were a good starting point to uncover gaps in students' understanding, be it in terms of their conceptualization of the issue or support engagement in desired practices.…”
Section: Discussionsupporting
confidence: 89%
“…A virtual collaborative space allowed us to collect rich data to understand how groups supported one another. Future work exploring the integration of hard and soft scaffolds in these workspaces is needed, particularly in exploring other forms of distributed scaffolds (Martin et al, 2019; Reiser & Tabak, 2014).…”
Section: Implications For Practice and Future Researchmentioning
confidence: 99%
“…Researchers have frequently framed guidance in inquiry-based science teaching within the scaffolding construct (Hmelo-Silver et al, 2007). In the scaffolding literature, both material scaffolds and an adult's verbal scaffolds are considered effective in guiding children's learning (van de Pol et al, 2010;Martin et al, 2019). Accordingly, guided play can take at least two different forms (Weisberg et al, 2016), guided play with material scaffolds only, and guided play with additional verbal scaffolds.…”
Section: Materials and Verbal Scaffolds In Guided Playmentioning
confidence: 99%
“…In guided play with additional verbal scaffolds, the adult not only provides materials but additionally plays along with the children, supports the children's play verbally and encourages higher order thinking (Chin, 2007;Haden, 2010;Kleickmann et al, 2016;Weisberg et al, 2016;Martin et al, 2019). The adult can use a set of verbal scaffolding techniques to aid children's cognitive activities (for an overview cf.…”
Section: Materials and Verbal Scaffolds In Guided Playmentioning
confidence: 99%
“…A recent study has illustrated the importance of the teacher complementing the scaffolding available in the system with further scaffolding that better respects the needs of the individual learner, rather than simply extending the kind of scaffolding already provided by the system (Martin, Tissenbaum, Gnesdilow, & Puntambekar, ). Note the finding from (Ma et al , ), described in the Introduction, that “Significant, positive mean effect sizes were found regardless of whether the ILE was used as the principal means of instruction, a supplement to teacher‐led instruction, an integral component of teacher‐led instruction … [my emphasis].”…”
Section: Screen‐level and Orchestration‐levelmentioning
confidence: 99%